Size Effect and Material Property Effect of the Impactor on the Damage Modes of the Single-Layer Kiewitt-8 Reticulated Dome - Li Lin; Feng Fan; XuDong Zhi; HongFeng Yin (The Scientific World Journal)
The dynamic response of large space structures under accidental impact has been the subject of intense research since the occurrence of the 9/11 incident. In the present paper, using the 3D ANSYS/LS-DYNA, size effect and material property effect of the impactor on the damage modes of the single-layer Kiewitt-8 reticulated dome were investigated, respectively, where the impactor was the cylinder and the impact direction was vertical. Firstly, analytical results with the rigid impactor indicated that the impactor size can change the damage mode of the reticulated dome. It was found that the probability happening to the global collapse has an obvious rise with the size increase of the impactor. Furthermore, the deformable impactor was considered to figure out the difference with the rigid impactor; the comparisons indicated that the deformable impactor, which has the same mass and the same striking velocity with the rigid impactor, can contribute to the occurrence of the global collapse at a certain initial striking condition.